Employing Project Work in a Vietnamese EFL Undergraduate Class to Promote Autonomy (Journal of Contemporary Educational Policies and Practices, 2022)
This paper investigates an attempt to stimulate autonomous practices among EFL (English as a Foreign Language) learners in Vietnam. While recent educational policies have advocated the development of learner autonomy in English language teaching and learning, approaches taken to support autonomy can sometimes be limited. In this paper, we reported the participation of one teaching colleague and twenty-six students in an action research project. Data sources included two rounds of interview and test between which a project work was conducted. Autonomy-supporting priorities included goal setting, planning, implementing and evaluation. The findings indicated that traditional pedagogy impacts on language learner autonomy to some extent. However, there was strong evidence that the development of project work can help Vietnamese learners to take greater control over their own learning. Pedagogical practices of autonomous learning through the use of project work in Vietnam and the region are suggested.